Meta-analysis of the relationship between dietary starch intake and enteric methane emissions in cattle from in vivo experiments (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Different sources and levels of starch in the total mixed ration might result in different rumen fermentation profiles, rumen microbial composition, and enteric methane production. The current study aimed to evaluate the effect of dietary starch intake on enteric methane production through a meta-analytical approach by integrating related published studies. Materials and Methods: Papers that provided study results on enteric methane production from cattle fed different sources and levels of starch were selected. A total of 52 publications were filtered based on some specified criteria, comprised of 73 studies focused on enteric methane production in cattle fed a basal diet supplemented with starch. The collected data were subjected to statistical meta-analysis through a mixed methodology model. The p-value and root mean square error (RMSE) were applied as the statistical models. Results: Results showed that increasing the level of dietary starch intake and its digestibility in the rumen as well as increasing propionate significantly decreased the acetate to propionate (A/P) ratio as well as enteric methane production (p < 0.01). Conclusions: It is concluded that the addition of starch to diets mitigates enteric methane production from cattle, primarily through two ways, i.e., manipulation of the protozoa population and alteration to a lower A/P ratio.Adv. Vet. Anim. Res., 11(1): 212-230, March 2024   http://doi.org/10.5455/javar.2024.k767